2007
DOI: 10.1111/j.1365-3040.2007.01738.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relationship between respiratory acclimation to the cold and photosystem II redox poise in Arabidopsis thaliana

Abstract: We examined the effect of manipulating photosystem II (PSII) redox poise on respiratory flux in leaves of Arabidopsis thaliana. Measurements were made on wild-type (WT) plants and npq4 mutant plants deficient in nonphotochemical quenching (NPQ). Two experiments were carried out. In the first experiment, WT and mutant warmgrown plants were exposed to three different irradiance regimes [75, 150 and 300 mmol photosynthetically active radiation (PAR)], and leaf dark respiration was measured in conjunction with PSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…In contrast, Bolstad et al (1999) reported no consistent trend of Q 10 values with respect to canopy position. Similarly, no evidence of irradiance-mediated changes in the Q 10 leaf R dark have been found in recent studies using herbaceous plants, and deciduous and evergreen tree species where substrate concentrations remained similar in high and low-light grown plants (Hartley et al 2006;Armstrong et al 2007;Zaragoza-Castells et al 2007.…”
Section: Introductionmentioning
confidence: 77%
“…In contrast, Bolstad et al (1999) reported no consistent trend of Q 10 values with respect to canopy position. Similarly, no evidence of irradiance-mediated changes in the Q 10 leaf R dark have been found in recent studies using herbaceous plants, and deciduous and evergreen tree species where substrate concentrations remained similar in high and low-light grown plants (Hartley et al 2006;Armstrong et al 2007;Zaragoza-Castells et al 2007.…”
Section: Introductionmentioning
confidence: 77%
“…Growth under low temperatures often results in significant alterations in leaf morphology. The most noticeable effect is a reduction in specific leaf area (the ratio of leaf area to leaf dry mass) [25]. It is also remarkable that under cold conditions the leaves become thicker than those observed under control or high temperature (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This result suggests that overall changes in respiratory capacity meant to modulate R L , and hence EP, also have some lasting influence on R D , as might be expected. A previous study found no compelling relationship between R D and EP ( R L was not examined), although in that study respiration was not being manipulated and, in fact, was relatively constant across the plant lines and growth conditions tested, which also did not include drought (Armstrong et al ., ).…”
Section: Discussionmentioning
confidence: 97%